2018
DOI: 10.1111/jsr.12720
|View full text |Cite
|
Sign up to set email alerts
|

Periodic limb movements during sleep are associated with cardiovascular diseases: A systematic review and meta‐analysis

Abstract: Periodic limb movements during sleep present with repetitive movements, typically in the lower limbs, during sleep. Periodic limb movements during sleep have been proposed to be associated with increased risk of heart diseases. The aim of this study was to examine the co-morbidity rates of heart disease, including acute myocardial infarction, coronary artery disease and cardiovascular disease, in subjects with or without periodic limb movements during sleep through a meta-analysis. An electronic review of PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
(77 reference statements)
1
11
0
Order By: Relevance
“…When RLS symptom duration was analyzed in a prospective study of 70,977 women free from coronary heart disease at baseline and followed for 6 years, patients with symptoms lasting for at least 3 years showed an increased risk of coronary heart disease (multivariable‐adjusted HR,1.80; 95% CI, 1.07–3.01) 93 . Lastly, a systematic review and meta‐analysis including cross‐sectional and prospective studies on PLMS found a significantly elevated prevalence of coronary artery disease (odds ratio, 1.56; 95% CI, 1.2–2.1) and cardiovascular disease in the study population (odds ratio, 1.27; 95% CI, 1.1–1.5) 94 …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…When RLS symptom duration was analyzed in a prospective study of 70,977 women free from coronary heart disease at baseline and followed for 6 years, patients with symptoms lasting for at least 3 years showed an increased risk of coronary heart disease (multivariable‐adjusted HR,1.80; 95% CI, 1.07–3.01) 93 . Lastly, a systematic review and meta‐analysis including cross‐sectional and prospective studies on PLMS found a significantly elevated prevalence of coronary artery disease (odds ratio, 1.56; 95% CI, 1.2–2.1) and cardiovascular disease in the study population (odds ratio, 1.27; 95% CI, 1.1–1.5) 94 …”
Section: Resultsmentioning
confidence: 95%
“…93 Lastly, a systematic review and meta-analysis including cross-sectional and prospective studies on PLMS found a significantly elevated prevalence of coronary artery disease (odds ratio, 1.56; 95% CI, 1.2-2.1) and cardiovascular disease in the study population (odds ratio, 1.27; 95% CI, 1.1-1.5). 94 RLS may favor cardiovascular disease through autonomic changes, modifying cardiovagal control, specific to arterial baroreflex, leading to greater peripheral vascular resistance and sympathetic overactivity [95][96][97] and ultimately increasing cardiovascular disease prevalence. 95 A recent cross-sectional study of a large population-based cohort of health outcomes in the Canadian general population aged 45 to 85 years found that the mean carotid intima-media thickness, an objective measure of atherosclerosis, was higher in the group of patients with probable RLS (0.755 ± 0.17; n = 2047) in comparison with a control group (0.736 ± 0.17; n = 24257) with an adjusted mean difference of 0.016 (95% CI, 0.008-0.024).…”
Section: Restless Legs Syndrome and Periodic Leg Movements Of Sleep (Rls-plms)mentioning
confidence: 99%
“…It has long been known that periodic leg movements during sleep (PLMS) are accompanied by transient increases in heart rate (HR; Ferri et al., 2007; Winkelman, 1999) and blood pressure (Pennestri et al., 2007; Siddiqui et al., 2007). In recent years, an increasing number of reports have been published on cardiovascular correlates of PLMS (Huang et al., 2019). These correlates support the hypothesis that PLMS have long‐term consequences on health.…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ there were significantly higher co-morbidity rates of coronary artery disease and cardiovascular diseases (CVD), but not acute myocardial infarction, in subjects with PLMS 22 . Meanwhile, these PLMS-related complications and/ or sequelae might also contribute to tinnitus formation 2,3,5-7 .…”
mentioning
confidence: 99%